Analisis Faktor yang Berhubungan dengan Kejadian Berat Badan Lahir Rendah (BBLR) di RSUD Bangkinang Kabupaten Kampar - Syahda, Syukrianti; Hastuty, Milda; Parmin, Joria (Universitas Pahlawan Tuanku Tambusai, 2024)
Birth weight is an indicator of the short-term and long-term health status of a newborn. It is estimated that 15 to 20% of newborns in the world are LBW, which means more than 20 million births per year. In Indonesia, of all reported neonatal deaths, 72.0% (20,266 deaths) occurred at the age of 0-28 days.The aim of this research is to find outanalysis of factors associated with the incidence of Low Birth Weight (LBW) in Bangkinang District Hospital. This research is quantitative analytical with case control type. The population in this study was all 124 newborn babies born in 2022 with a sample size of 124 people. The sampling technique uses total sampling. The research results obtained were that there was a relationship between age (pvalue: 0.009), parity (pvalue: 0.000), preeclampsia (pvalue: 0.010) and anemia (pvalue: 0.000) with the incidence of LBW. Meanwhile, for the employment variable, there is no relationship (pvalue: 0.445) with the incidence of LBW. ExpectedMothers should be able to plan a pregnancy within the age range of 20-35 years, parity 1-3, and diligently check their pregnancies regularly.